2007
DOI: 10.1007/s10067-006-0479-8
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian-Portuguese version of the Health Assessment Questionnaire for Spondyloarthropathies (HAQ-S) in patients with ankylosing spondylitis: a translation, cross-cultural adaptation, and validation

Abstract: To translate and cross-culturally adapt to the Brazilian-Portuguese language (BP), five items were added to Health Assessment Questionnaire (HAQ) to validate the resulting HAQ-S BP version for ankylosing spondylitis (AS). The items were translated into BP following translation and back-translation. To assess validity, 25 patients were evaluated using the HAQ, Bath AS Functional Index (BASFI), Bath AS Disease Activity Index (BASDAI), Bath AS Metrology Index (BASMI), and laboratory variables (erythrocyte sedimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
3
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 4 publications
0
13
3
1
Order By: Relevance
“…[5] Regarding the psychometric properties, the results of the test/re-test in our study was significantly smaller than that of the Brazilian-Portuguese version (0.99), [18] but it was comparable to the Tunisian version (0.84). The Arabic version of the PI HAQ showed Kappa statistics between 96.2 and 98.9.…”
Section: Discussioncontrasting
confidence: 57%
“…[5] Regarding the psychometric properties, the results of the test/re-test in our study was significantly smaller than that of the Brazilian-Portuguese version (0.99), [18] but it was comparable to the Tunisian version (0.84). The Arabic version of the PI HAQ showed Kappa statistics between 96.2 and 98.9.…”
Section: Discussioncontrasting
confidence: 57%
“…In 2010, the Brazilian National Health Questionnaire-Disability Index (HAQ) [11,12] and by the EuroQol-5D (EQ-5D), respectively.…”
mentioning
confidence: 99%
“…This is why we decided that the term "alÂoverio pooetleri" was more convenient. A similar problem in the Wrst question was reported in the Brazil-Portuguese adaptation of HAQ-S. Shinjo et al [9] stated that the term "grocery bags" was not a term used in Brazil or Portugal, and they translated it into a term meaning "supermarket bags".…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, Shinjo et al [9] found the total HAQ-S score higher than the total HAQ score. Both Daltroy et al [1] and Shinjo et al [9] found that the mean scores of the added two subcategories were higher than the mean scores of the other categories. Similarly in our study, the mean scores of the added two subcategories were found to be higher than the mean scores of the other categories.…”
Section: Discussionmentioning
confidence: 95%